Comparative analysis of a two-dimensional and three-dimensional model of BT-20 triple negative breast carcinoma cells in response to an antiproliferative agent - Cordier, Werner (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2018.